EFFECTS OF FOOD FROM MULBERRY TREATED WITH UREA “N” ON LARVAL DEVELOPMENT AND COCOON WEIGHT OF SILKWORM BOMBYX MORI L. - Mahmood, Rashid; Mahmood, Rashid; Jan, Muhammad Tahir; Khan, Muhammad Idrees (Journal of Research (Science), 2001)
Silkworm larvae fed on leaves, from mulberry (Morus laevigata L.) tree, given soil treatment with 0.2%N concentration, consumed significant more food, gained more weight and produced heavier cocoons, as compared to those fed on leaves from trees treated with 0.1%N, 0.3%N, 0.4 %N concentrations.